Keparahan Penyakit Blas Pyricularia oryzae dan Analisis Gen Virulensi Menggunakan Metode Sequence Characterized Amplified Region - Kurrata, Gilang; Tutik Kuswinanti; Andi Nasruddin (Jurnal Fitopatologi Indonesia, 2021)
Severity of Blast Disease and Analysis of Virulence Gene Using Sequence Characterized Amplified Region Method Rice blast disease caused by the fungus Pyricularia oryzae (teleomorph: Magnaporthe oryzae) is one of the important diseases in rice cultivation in the world, including Indonesia. The use of resistant varieties is a way to deal with blast disease since it is cheap, efficient and safe from the risk of pesticide pollution. However, the resistance of a rice variety to blast disease can only be utilized for a few years due to the complexity of pathogens which can easily break down the resistance of a variety, especially if their resistance is determined only by one dominant gene. The aims of this research was to determine the severity of blast disease and genetic variation of P. oryzae isolates from Maros District and the relationship between disease severity and haplotype variety obtained as the basis for recommendations for control with site-specific resistant varieties. The severity of blast disease was observed using the Standard Evaluation System for Rice was carried out in 8 locations (different sub-districts) in Maros District, South Sulawesi from June to September 2019. The pathogen’s genetic diversity was determined using specific primers, coding the fungus virulence genes namely Pwl2, Erg2 and Cut1. The highest leaf blast intensity was observed on var. Mekongga in Simbang sub-district (42.12%) and Maros Baru sub-district (23.33%). In Tanralili sub-district (Inpari-7) and Mandai sub-district (var. Ciherang) leaf blast intencity were 7.6% and 7.88% respectively. A total of 15 isolates of P. oryzae obtained from 8 sub-districts in Maros. Analysis of genetic diversity showed found 5 different haplotypes, namely haplotype A-000 (4 isolates), C-011 (3 isolates), D-111 (2 isolates), F-110 (3 isolates) and G-100 (3 isolates).